Quantification of anaerobic digestion feedstocks for a regional bioeconomy. Issue 4 (16th November 2018) - Curry, Robin; Pérez-Camacho, María Natividad; Brennan, Robert; Gilkinson, Stephen; Cromie, Thomas; Foster, Percy; Smyth, Beatrice; Orozco, Angela; Groom, Elaine; Murray, Simon; Hanna, Julie-Ann; Kelly, Mark; et al.
Abstract : Anaerobic digestion (AD) for biogas production forms one of the fundamental building blocks of the bioeconomy, and a research programme has been under way in Northern Ireland, which culminated in the publication of a Biogas Research Action Plan 2020 in 2014. One important element of this programme was the identification of the need for an evidence base for the potential bioresource feedstocks. This paper reports the outputs of the quantification of feedstocks for AD research, which has identified the organic feedstocks available for biogas production on a regional basis and categorised these as: organic (biodegradable) fraction of municipal solid waste, sewage sludge, organic industrial and commercial wastes, manure from livestock, food wastes and energy crops. The research study further quantified the biogas and energy potential of these feedstocks and possible reductions in greenhouse gas emissions. The limitations of the research study are acknowledged and opportunities to address these and build on and extend the study are identified, including feedstocks for other bioeconomy processes and the application and further development of the biorefinery concept.